Lead isotopes as a palaeodietary tracer in southwestern South Africa - Scott, Mari (Department of Geological Sciences, 2019)
This thesis evaluates the utility of lead (Pb) isotopes, in combination with strontium (Sr) isotopes, as a geochemical tracer for studying the palaeodiets and palaeo-landscape usage in southwestern South Africa. Isotopes of light elements, carbon (C), nitrogen (N), oxygen (O), and sulphur (S), are widely used as (palaeo) environmental tracers, but do not yield information on the geological substrates on which individuals have lived. Sr isotopes in bones and teeth are useful in distinguishing between areas of distinct bedrock geology, however, the efficiency of Sr is limited at near-coastal areas, which forms a major part of this study area. This is because Sr has a relatively high concentration and long residence time in seawater. In addition, coastal soils contain not only aerosol-derived marine Sr, but frequently also include fragments of shells and other marine carbonates, so their 87Sr/86Sr is like the ocean. This study analysed Pb and Sr concentrations and isotopic compositions of animals and plants derived from the various geological substrates of southwestern South Africa. In order to do this, a detailed Sr-Pb separation scheme was developed, involving the separation and pre-concentration of Sr and Pb from a single digested sample by means of ion-exchange chromatography. Elemental concentrations were measured with a Thermo X-series II quadrupole ICP-MS instrument. Sr concentrations ranged between 111 ppm and 1862 ppm, while Pb concentrations were lower, ranging between 0.012 ppm and 2.30 ppm. Isotopic ratios were determined by means of a Nu Instruments high resolution multi-collector inductively-coupled plasma mass spectrometry (HR-MC-ICP-MS). Samples were introduced into the system as solutions, producing an order of magnitude more precise results than laser ablation analysis on the same material. Sr isotopes are useful for distinguishing between individuals living in near-coastal environments and those living further inland, while Pb isotopes could differentiate between granites and shales/sandstones. Pb isotopes proved to be a valuable palaeodietary tracer and can be used in combination with Sr isotopes to extent our knowledge of palaeo-landscape usage at coastal-marine environments.